Copper(II) hydrazone complexes with different nuclearities and geometries: Synthesis, structural characterization, antioxidant SOD activity and antiproliferative properties. (1st August 2020) - Patel, A.K.; Jadeja, R.N.; Roy, H.; Patel, R.N.; Patel, S.K.; Butcher, R.J.; Cortijo, M.; Herrero, S.
Graphical abstract: Two new mono and binuclear copper(II) complexes were synthesized by a biomimetic strategy and their structures were solved by single-crystal X-ray crystallography and various spectral techniques. Both complexes have pentacoordinate geometries. Low-temperature susceptibility measurements revealed that the copper(II) centers in both complexes are weakly antiferromagnetically coupled. Their antioxidant SOD and anticancer activities were also examined. Both complexes are potent SOD mimics and display anticancer activity. Highlights: Synthesis and characterization of two copper(II) hydrazone complexes. The copper complexes are mono and binuclear, having distorted square pyramidal geometries. Both complexes show a weak anti-ferromagnetic interaction. Both complexes catalyzed the dismutation of superoxide ( O 2 ∙ - ). Both complexes show good cytotoxicity against cancers cell lines. Abstract: New copper(II) hydrazone complexes with (Z)-2-(phenyl(2-(pyridin-2-yl)hydrazono)methyl)pyridine (L) were synthesized and characterized using various physicochemical methods. The geometries of the complexes can be classified as mononuclear and binuclear. The complex 1, [Cu(L)(Cl)2 ], is mononuclear whereas the solid-state structure of complex 2 contain a mixture of co-crystals of the mono- and binuclear complexes 2a, [Cu(L)(H2 O)(SO4 )], and 2b, [Cu2 (L)2 (μ-SO4 )2 ]. The unit cell of 2 contains two units of the mononuclear complex 2a and one units of the binuclear complex 2b . The copper atoms contained in all the mono- and binuclear complexes are in a distorted square pyramidal geometry. The present study indicates that complexes having different nuclearities and geometries can be achieved by changing the synthetic conditions and methods. Variable temperature magnetic susceptibility measurements of the complexes have shown the presence of weak anti-ferromagnetic interactions. These interactions are mediated by intermolecular hydrogen bonding in 1 and through a symmetric sulfate bridge in 2 . The EPR spectra in the polycrystalline state for 1 and 2 exhibited a broad signal at 2.149 due to spin–spin interactions between two copper(II) ions. The cyclic voltammograms of complexes 1 and 2 in DMSO gave two irreversible redox waves. Density functional theory (DFT) calculations were evaluated in the study, involving the molecular specification with the use of B3LYP/LANL2DZ formalism for the copper atoms and B3LYP/6-31G for the remaining atoms. Both complexes catalyzed the dismutation of superoxide ( O 2 ∙ - ). Furthermore, the copper complexes and the ligand were tested to explore their anticancer properties. Promising cytotoxicity of the synthesized compounds was observed against the selected cancerous cell lines of neuroblastoma, lung carcinoma, hepatocellular carcinoma and breast cancer.